1994
DOI: 10.1007/bf02244997
|View full text |Cite
|
Sign up to set email alerts
|

Effects of (R)-α-methylhistamine and scopolamine on spatial learning in the rat assessed using a water maze

Abstract: The effects of (R)-alpha-methylhistamine ((R)-alpha-MeHA, a selective H3-receptor agonist) and scopolamine (SCOP, a muscarinic antagonist) were investigated on spatial learning and memory in the rat (Hooded Lister) using a water maze (WM). (R)-alpha-MeHA treatment (6.3 and 10 mg/kg IP) had no apparent effect on spatial learning but did result in enhanced spatial recall at the higher dose, assessed by a transfer (probe) test after training. In contrast, SCOP (0.5 mg/kg IP) induced a learning and memory deficit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
1

Year Published

1995
1995
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 37 publications
4
13
1
Order By: Relevance
“…Interestingly, bilateral lesions of the tuberomammilary nucleus produce facilitation of learning (Klapdor et al, 1994). In contrast to the hypothesis that histamine impairs cognitive functions, other studies suggest the positive role of the histaminergic system on learning and memory (Kamei et al, 1993), and of RAMH in enhancing spatial learning in a water maze test (Smith et al, 1994). Differences among the behavioural tests explain the discrepancies.…”
Section: Discussioncontrasting
confidence: 44%
“…Interestingly, bilateral lesions of the tuberomammilary nucleus produce facilitation of learning (Klapdor et al, 1994). In contrast to the hypothesis that histamine impairs cognitive functions, other studies suggest the positive role of the histaminergic system on learning and memory (Kamei et al, 1993), and of RAMH in enhancing spatial learning in a water maze test (Smith et al, 1994). Differences among the behavioural tests explain the discrepancies.…”
Section: Discussioncontrasting
confidence: 44%
“…Several studies in the past several years (with histamine receptor ligands) have indicated that the endogenous autacoid, histamine, may also play an important role in learning and memory, as well as a number of other functions in the CNS [Smith et al, 1994;Miyazaki et al, 1995]. Therefore, studies to further elucidate the biochemical effects as well as behavioral effects of JWS (and related compounds) are warranted.…”
Section: Discussionsupporting
confidence: 41%
“…It should be kept in mind, though, that the systemic administration of these histaminergic compounds can not account for a selective action on restricted brain regions. The scenario is certainly more complex; indeed, R-a-methylhistamine-induced improvement of rat performance in a water maze test [117] calls for a different explanation than simple ACh/histamine interactions. R-a-methylhistamine modulates, in addition to ACh, the release of either 5-HT or noradrenaline [114], and each of these transmitters has been shown to alter performance in a variety of cognitive tests [33].…”
Section: Discussionmentioning
confidence: 42%
“…Therefore, the impairment of cognition by H 3 receptor agonists is unlikely attributable solely to the modulation of cortical acetylcholine. One might envisage mechanisms other than the cholinergic one, and the finding that R-amethylhistamine improved rodent spatial learning and memory, assessed using a water maze [117], supports this contention. Spatial learning is a primary function of the rodent hippocampus [90], and the water maze test is exquisitely sensitive to hippocampal lesions [87], but H 3 receptor stimulation is expected to decrease hippocampal cholinergic activity [6,7].…”
Section: Histamine and Cognitionmentioning
confidence: 44%